2010
DOI: 10.1093/eurheartj/ehq032
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in adult congenital heart disease

Abstract: Mortality is increased in adults with congenital heart disease, particularly in the young. The vast majority die from cardiovascular causes. Mortality risk, particularly by heart failure, is increased by virtually all complications. Complications are equally hazardous in younger as in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
295
5
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(313 citation statements)
references
References 34 publications
8
295
5
5
Order By: Relevance
“…Adults with CHD (ACHD) have premature morbidity and mortality and often die from cardiovascular events 2. In this aging ACHD population, acquired heart disease, such as atherosclerotic coronary artery disease, may contribute to this risk.…”
Section: Introductionmentioning
confidence: 99%
“…Adults with CHD (ACHD) have premature morbidity and mortality and often die from cardiovascular events 2. In this aging ACHD population, acquired heart disease, such as atherosclerotic coronary artery disease, may contribute to this risk.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that these GATA6 DSVs may be involved in VSD formation by changing GATA6 levels as a risk factor. As morbidity and mortality in adult CHD patients are significantly higher than general populations, likely due to genetic defects [54,55], genetic studies may provide insight into designing novel therapies for adult CHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the patients in the 30-50 year old group had selected themselves by having mild forms of septal defects without the added comorbidities of older age. Verheugt et al [4] investigated the causes of mortality in this unique patient population by linking the Dutch national registry for ACHD patients with the national death registry between the years 2002-2009. They found excessive mortality associated with ACHD when compared to the general population.…”
Section: Peri Procedural Risk Assessment and Stratificationmentioning
confidence: 99%